Hurdle step test: Convergent validity and ability to discriminate between subjects with different levels of postural stability (preliminary results) - Bhudarally, Maria; Atalaia, Tiago; Abrantes, João; Aleixo, Pedro (Gait & posture, 2023)
The Hurdle Step test (HS) is one of the seven tests included in the Functional Movement Screen (FMS), a widely used clinical tool that assesses joint mobility and postural stability deficits.(1) However, there is the need to study FMS validity.(2) Convergent validity is defined as how closely the scale is associated with other measures of the same construct,(3) demonstrated by a high correlation between them.(4) HS aims to assess postural stability during an unipedal stance.(1) Postural stability refers to the ability of a self-controlled body to maintain adequate movement sustainability.(5) Kinematic parameters of the centre of pressure (CoP) and centre of gravity projection (CoGp) have been used to study postural stability.(6–8) To the best of our knowledge, no research has studied the relation between HS score and biomechanical parameters related to postural stability. Does HS present convergent validity regarding postural stability and the ability to discriminate between subjects with different levels of stability? Twenty-six healthy subjects were included (22.2±1.7 years; 3 women). Subjects performed five repetitions of the HS for each lower limb according to the FMS guidelines.(1) Subjects scored as “0” or injured were excluded. Subjects’ performances in frontal and sagittal plane were recorded using two cameras and afterwards scored by two FMS certificated evaluators. The kinematic parameters of the CoP and CoGp presented in Table 1 were collected using a 3D motion analysis system (Vicon®;200Hz) and a force plate (AMTI;1000Hz). These parameters were studied during the stance phase of the forward (phase 1) and backward step (phase 2). Spearman's coefficient studied the correlation between HS score and biomechanical parameters. Mann-Whitney test assessed the ability of HS to discriminate between subjects with different scores (“1”,“2”,“3”). [Display omitted] No subject was scored as “1”. Fig. 1 shows the CoGp and CoP displacements in the horizontal plane (examples of a subject scored as “2” and a subject scored as “3”). HS scores presented low to moderate correlations with: CoP-CoGp average anteroposterior distance (R=0.552;p<0.05), CoP average anteroposterior velocity (R=-0.282;p<0.05); CoGp average mediolateral (R=-0.280;p<0.05) and anteroposterior velocity (R=-0.397;p<0.05), CoGp anteroposterior velocity peak (R=-0.439;p<0.05), CoP sum of mediolateral displacements (R=0.319;p<0.05), CoP range of anteroposterior displacement (R=-0.293;p<0.05), CoP-CoGp range of mediolateral (R=-0.276;p<0.05) and anteroposterior distance (R=-0.434;p<0.05), and CoP-CoGp range of distance (R=-0.312;p<0.05) – phase 1; CoGp average anteroposterior velocity (R=-0.279;p<0.05) and CoP-CoGp average anteroposterior distance (R=0.444;p<0.05) – phase 2; the other biomechanical parameters presented no correlations. Differences between groups of subjects scored as “2” or “3” are presented in Table 1. HS presented low convergent validity regarding postural stability. Although HS has shown some ability to discriminate subjects with different levels of postural stability, the fact that there were no subjects scored as “1” may indicate some limitations of the test to discriminate subjects at more levels.